Perlindungan Hak Asasi Manusia Terhadap Eksploitasi Anak Bawah Umur Ditinjau Secara Yuridis - Salmanita Shalsabella Pramudita; Tiara Rachma Sari; Mulyadi Mulyadi (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
Children are God's gifts that must be protected and loved. Today there are many cases of violence against children, often even within their own families. This is usually due to family and economic factors in the family in the child. In addition, the number of abused children often shows a correlation with the number of child workers in Indonesia. This study discusses violence against children from a human rights perspective. This study uses a normative legal approach, which explains legal science and social science related to violence against children and child protection. The results of this study indicate that violence against children increases child mortality in Indonesia The method used is normative, namely those made to legal standards contained in statutory regulations. In this method there are several discussions regarding the legal provisions, Law no. 35 of 2014 concerning Child Protection..